The Effect of Competence and Work Environment on Organizational Performance through Work Motivation as a Mediation Variable in Jatisampurna District, Bekasi City - Muhammad Faisal; Imam Wibowo (Krisnadwipayana International Journal of Management Studies, 2022)
This study uses a quantitative approach with the method of path analysis. The population in this studywere all civil servants in Jatisampurna District, Bekasi City. There were as many as 68 employees witha non-probability sampling method, using a qualitative data collection stage (questionnaire) to becomequantitative data values on a semantic differential scale. The results of the study are as follows, 1). Theresults of research on the effect of competence on work motivation have negative and significantresults. 2). The results of the research on the influence of the work environment on work motivationhave a positive and significant effect. 3). The results of competency research on organizationalperformance are positive and significant. 4). The results of the work environment research onorganizational performance are negative and significant. 5). The results of the research on workmotivation on organizational performance are positive and significant. 6) The results of the researchon competence and the environment on work motivation are positive and significant. 7). The resultsof the research on competence and work environment on organizational performance are positive andsignificant. 8). The results of the research on the effect of competence on organizational performancethrough work motivation are positive and significant. 9). The results of research on the effect of thework environment on organizational performance through work motivation are positive andsignificant.